Photoluminescence and optical dispersion parameters of N-doped ZnO nano-fiber thin films - Abd El-saddek, M. S.; Yahia, I. S.; Alahmed, Z. A.; Yakuphanoğlu, Fahrettin (Springer, 2013)
N-doped ZnO (NZO) nanocrystalline thin films were successfully synthesized via sol-gel method. The structural and optical properties of the films were characterized by various techniques including X-ray diffraction, atomic force microscopy (AFM), UV-vis absorption and photoluminescence. The UV-vis absorption edge was changed with increasing N-doping concentration. X-ray diffraction (XRD) results clearly showed that the zinc oxide doped with nitrogen (5 to 20 wt.%) were identified with phases of hexagonal ZnO and N-doped ZnO nanocrystalline thin films. The refractive index dispersion mechanism obeys the Single oscillator model. The dispersion parameters E (o) and E (d) of the thin films were determined. The dispersion parameters were changed by N dopant. It is evaluated that the structural, optical constants, photoluminescence properties of Zinc oxide film can be controlled by N dopants.
Keywords: ZnO nanocrystalline; N-doped ZnO; Sol-gel calcinations method; Spin coating; Optical properties; Photoluminescence spectroscopy